Analisa Komparasi Sifat Fisis dan Mekanis Piston Sepeda Motor dari Empat Pabrikan - Suherman, Suherman; Mizhar, Susri; Putra, Andi; Sutiman, Sutiman; Arifin, Zainal (Jurnal Pendidikan Vokasi Otomotif, 2024)
The piston is an essential component in the internal combustion system. Unfortunately, most piston products on the market are of low quality, which is detrimental to consumers. Most pistons sold in spare parts shops in Medan City have varying prices and different quality. The study compares four manufacturers' chemical composition, microstructure and hardness of the pistons of 4-stroke motorcycles. The four types of pistons were purchased at an automotive component sales shop in Medan city. The pistons were cut by machine and then analyzed for chemical composition, microstructure and hardness. The research results show that the chemical composition of the four-piston manufacturers is almost similar, where the silicon content ranges from 2-3%, which is a hypoeutectic Al-Si aluminium alloy. Interestingly, the hardness values and microstructure of pistons are different. The hardness value for brand X is the highest compared to other products, at 41.16 VHN. Microstructural observations show that the microstructures of manufacturers W, X and Y are similar, where the Si particles are evenly distributed with almost uniform sizes. Meanwhile, the Z manufacturer shows a microstructure with fibrous Si particles with a coarse SDAS size.